The application of English-Bahasa Indonesia compatibility in descriptive text to improve writing skill of grade VII 19 Junior High School, Bandung, academic year 2020-2021 - Purnomowulan, R. R. (Technium Social Sciences Journal, 2023)
Classroom Action Research in “The application of English-bahasa Indonesia compatibility in descriptive text to improve writing skill of Grade VII 19 Junior High School Bandung, Indonesia, in academic year 2020-2021” is purposed to intensify students’s competencies both in writing bahasa Indonesia and English. Classroom Action Reseach at this moment was undertaken in Bandung, from November 2016 until April 2017. It took six months to accomplish the purpose of this study. The mayor participants were Grade VII. with 250 students had participated in this study. This classroom action research activities had to be varied with daily activities in learning English, this cycle had been implemented in the early, middle, or in the end of English lesson.Based on the three cycles implemented in applying English- bahasa Indonesia compatibility in writing descriptive text to improve writing skill, most students has gradually improved their achievement in writing the text.